Evaluation of the Implementation of Outpatient Electronic Medical Records - Rosita, Riska; Risqika, Azzahra Mifta; Yuliani, Novita; Devhy , Ni Luh Putu (Universitas Muhammadiyah Sidoarjo, 2024)
The implementation of Electronic Medical Records (EMR) in X hospital has been running since 2022 but its use is still not optimal, especially in outpatient installations. This study aims to evaluate the implementation of outpatient EMR at X Hospital based on the HOT-FIT (Human, Organisation, Technology, and Net Benefit) framework. The research method with descriptive qualitative, uses a cross sectional approach. The research subjects were the head of medical records, head of outpatient polyclinic, head of outpatient registration, head of pharmacy, head of laboratory, doctor, head of cashier and head of IT team. The object of research was the implementation of outpatient EMR. Data collection through interviews and observations. The results showed that in the human aspect, there were still doctors who could not use EMR due to age. In the organization aspect, the standard operating procedures (SOPs) regarding EMR are still in draft form, have not been approved by the hospital director and have not been socialized. In the technology aspect, EMR system features that are not in accordance with user needs cause the output of health data information to be incomplete. The net-benefit aspect of RME, the use of EMR is more time efficient in health services and paperless. Conclusion, that the development of EMR at Hospital X is still ongoing, starting from improving the competence of medical personnel, organizational commitment, and improving the EMR system coding.